Разрушенные скелеты на могильнике Клин-Яр III на Северном Кавказе - Флёров, В.С. (Материалы по археологии, истории и этнографии Таврии, 1998)
A burial in side chamber N 29/1085 of Klin-Yar III cemetery in the Northern Caucasus, where the rite of neutralizing, making harmless, buried people by destroying a skeleton, is examined in this article. This rite is present in 16 out of 25 unearthed side chambers of the 5th - the beginning of the 8th centuries. It was displayed in different forms: from taking off the bones of feet up to the complete destroying .skeletons.